Sustainable valorization of citrus pomace waste: biochar production and in vitro bioactivities - Cristina Spedale; Vincenzo Chiofalo; Matteo Dell’Anno; Sara Frazzini; Marco Puglia; Simone Pedrazzi; Alessandra Moscatelli; Elisabetta Onelli; Luciana Rossi (Veterinary Research Communications, 2026)

Managing for conservation: The case study of Marsilea quadrifolia L. in wet meadows of Natura 2000 site (N Italy) - Anna Corli; Aurora Panizza; Simone Orsenigo; Silvano Lodetti; Graziano Rossi; Margherita Tognela (Journal for Nature Conservation, 2026)

Measuring bacterial oxygen consumption rate to probe metabolic signature and antimicrobial susceptibility - Chiara Scribani Rossi; Simone Angeli; Bruno Casciaro; Maria Rosa Loffredo; Maria Luisa Mangoni; Sharon Spizzichino; Giovanna Boumis; Manuel Espinosa-Urgel; Marzia Arese; Alessio Paone; Francesca Cutruzzolà; Serena Rinaldo (European Biophysics Journal, 2026)

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Nature-inspired biodegradation of poly(butylene succinate-co-adipate): the potential of Cladosporium psychrotolerans isolated from marine copepods - Luca Niccolini; Giampiero De Simone; Maurizia Seggiani; Niccoletta Barbani; Damiano Rossi; Miriam Cappello; David Levin; Federica Spina; Xiaojun Yan; Giulio Petroni; Isabella Buttino; Simona Di Gregorio (Environmental Science and Pollution Research, 2025)

Noninvasive Brain Stimulation in Primary Progressive Aphasia with and Without Concomitant Speech and Language Therapy: Systematic Review and Meta-analysis - Francesco Lomi; Ilaria Simonelli; Stefano Cappa; Patrizio Pasqualetti; Simone Rossi (Neuropsychology Review, 2025)
Primary progressive aphasias (PPA) represent a group of neurodegenerative conditions affecting verbal communication abilities for which no effective medication is currently available. Noninvasive brain stimulation (NiBS) has been mainly explored as adjunctive therapy to conventional speech and language therapy (SLT) with promising results. The present meta-analysis of randomized-controlled trials (RCTs) aims to evaluate the efficacy of NiBS in PPA patients on a range of linguistic tasks (naming, phonemic fluency, semantic fluency). A literature search was carried out using EMBASE and PUBMED, searching for multi-session RCTs administering NiBS on PPA patients as stand-alone or with SLT. The results were not significant overall, indicating a null difference between the active and the sham condition on language functions; pooled effects tended to be higher in parallel than in crossover studies and for follow-ups than post-treatment. In the naming analyses, the combined effects for the studies that coupled NiBS with SLT were slightly higher than the overall effect at each time point, although not significant. These results need to be considered with caution given the low number of included studies and small sample sizes, but offer relevant indications for future research in terms of optimal treatment protocols and personalization of therapies.

Prenatal exposure to fine particulate matter PM2.5 and small for gestational age: a Bayesian model for area-based data in Milan - Simone Colombara; Rossella Murtas; Sara Tunesi; Alessandra Guglielmi; Antonio Giampiero Russo; Paola Angelini; Serena Broccoli; Marco Monti; Nicola Caranci; Katia Raffaelli; Daniela Fortuna; Paolo Giorgi Rossi; et al. (Environmental and Ecological Statistics, 2025)

Sensing the Reducing Power to Determine the Cell Fate: Flavin Redox-Switches in Signal Transduction - Chiara Scribani-Rossi; Simone Angeli; Alessio Paone; Sharon Spizzichino; Federica Di Fonzo; Marzia Arese; Francesca Cutruzzolà; Alessandro Paiardini; Serena Rinaldo (Current Microbiology, 2025)
Balancing electron donors and acceptors is crucial for bacterial cell to control both anabolism and catabolism rates and to keep at minimum ROS production and the resulting oxidative stress. Efficiency of nutrients uptake and assimilation is therefore linked to the availability of electron acceptors, to finally re-cycle reduced intracellular electron shuttles belonging to catabolism via respiratory chain. In case of excess reduced electron shuttles (named high reducing power), partially reduced respiratory complexes can be populated, which in turn produce ROS and oxidative stress. This is particularly relevant in the biofilm structure, where the stratified community copes with variable environment characterized by nutrients and oxygen gradients; shortage of electron acceptors found in the deeper layers of bacterial biofilm potentially favors the intracellular increase in reducing power. To avoid this risk, bacterial biofilm promotes extracellular electron flux and re-shapes biofilm morphology to increase the surface in contact with oxygen (i.e., electron acceptors). Sensing the reducing power is therefore a strategy to re-adapt the cellular metabolism to the variation of the environmental conditions, to promote the production of defense systems scavenging ROS and finally to tune bacterial behavior, such as chemotaxis and biofilm morphology. In this review, the role of the flavins in sensing the reducing power via signal transducers is discussed, with a focus on selected examples deeply characterized so far. The possible interference of such sensing activity as a strategy to treat infections and biofilm by means of electroceutical tools, is also discussed as future perspective.

Impact of light intensity on purple phototrophic bacteria mixed cultures: experimental insights and biokinetic modelling - Ali Amini; Simone Rossi; Valiallah Amirian Mojarad; Gabriele Bellotti; Fabrizio Cappa; Filippo Vaccari; Edoardo Puglisi; Roberto Canziani; Elena Ficara; Andrea Turolla (Bioresource Technology, 2025)

Growth performances of gilthead seabream (Sparus aurata) fed alternative diets for “circular” land-based IMTA production - Lorenzo Rossi; Carlo Bibbiani; Francesca Conti; Chiara Sangiacomo; Ilaria Marchioni; Elisa Merega; Simone Mancini; Alberto Pardossi; Baldassare Fronte (Aquaculture, 2025)

Individual alpha frequency tACS modifies the detection of space–time optical illusion - Francesco Neri; Vincenzo Catrambone; Alessandra Cinti; Adriano Scoccia; Alberto Benelli; Sara Romanella; Laetitia Grabot; Gaetano Valenza; Carmelo Luca Smeralda; Emiliano Santarnecchi; Virginie van Wassenhove; Simone Rossi (Experimental Brain Research, 2025)
Postdiction is a perceptual phenomenon where the perception of an earlier stimulus is influenced by a later one. This effect is commonly studied using the ‘rabbit illusion’, in which temporally regular, but spatially irregular, stimuli are perceived as equidistant. While previous research has focused on short inter-stimulus intervals (100–200 ms), the role of longer intervals, which may engage late attentional processes, remains unexplored. This study investigates whether postdiction is purely perceptual or also involves attentional mechanisms by using visual stimuli separated by extended intervals. 33 participants (17 females) were assigned to two experimental groups with two different temporal inter-flash intervals (IFI) between stimuli (250 ms: 250-IFI group; 500 ms: 500-IFI). Two stimulation protocols of active transcranial electrical stimulation (tES) and one control condition were tested on the left precuneus/inferior parietal gyrus: (i) transcranial alternating current stimulation (tACS) at the individual alpha frequency (IAF) (IAF-tACS); (ii) transcranial random noise stimulation across the whole alpha band (i.e., 8–12 Hz, Alpha-tRNS) and (iii) a placebo (Sham) stimulation. The postdiction phenomenon was observable in both experimental groups. The participants in the 500-IFI group demonstrated enhanced performance in detecting the illusion during the rabbit illusion task when IAF-tACS was applied. The behavioral results suggest that attentional functions, beyond perceptual ones, play a key role in the postdiction phenomenon.

Adventively established Leptopilina japonica: a new opportunity for augmentative biocontrol of Drosophila suzukii - Marco Valerio Rossi-Stacconi; Paul K. Abram; Gianfranco Anfora; Elizabeth Beers; Antonio Biondi; Nicolas Borowiec; Juli Carrillo; Jana Collatz; Asia Colmagro; Benjamin Crossman Johnson; Kent Daane; Giovanni Dal Zotto; et al. (Journal of Pest Science, 2025)
The invasive spotted-wing drosophila, Drosophila suzukii , has emerged as a significant global pest over the past decade, threatening fruit production worldwide. The parasitoid Leptopilina japonica , presumed native to East Asia, has established adventive populations in Europe and North America and is increasingly recognized for its ability to parasitize substantial proportions of D. suzukii larvae across diverse habitats. Here, we provide a broad review of the biology, establishment, distribution, and potential impacts of L. japonica . Using field data from international monitoring programs, we document the seasonal dynamics of plant–host–parasitoid associations and assess evidence for L. japonica ’s impact on D. suzukii and non-target organisms. Findings indicate that L. japonica has successfully established in several areas where D. suzukii is present in Europe and North America, showing promise as a biological control agent to support sustainable pest management. Current data suggest it provides some suppression of D. suzukii populations with minimal non-target effects. However, long-term studies are necessary to clarify its food web interactions and efficacy as a biological control agent. In areas where L. japonica has been established, we propose its use in augmentative biological control programs to enhance its impacts in specific agricultural settings. Case-specific evaluations of its ecological effects and role in integrated pest management, supported by continued monitoring, are essential. The case of L. japonica illustrates the need for clear, research-informed policies to guide the use of adventively established non-indigenous natural enemies in pest management.

Forest Age Rivals Climate to Explain Reproductive Allocation Patterns in Forest Ecosystems Globally - Rachel E. Ward; Huanyuan Zhang‐Zheng; Kate Abernethy; Stephen Adu‐Bredu; Luzmilla Arroyo; Andrew Bailey; Jos Barlow; Erika Berenguer; Liana Chesini‐Rossi; Percival Cho; Cecilia A. L. Dahlsjö; Eder Carvalho das Neves; et al. (Ecology Letters, 2025)
Forest allocation of net primary productivity (NPP) to reproduction (carbon required for flowers, fruits, and seeds) is poorly quantified globally, despite its critical role in forest regeneration and a well‐supported trade‐off with allocation to growth. Here, we present the first global synthesis of a biometric proxy for forest reproductive allocation (RA) across environmental and stand age gradients from a compiled dataset of 824 observations across 393 sites. We find that ecosystem‐scale RA increases ~60% from boreal to tropical forests. Climate shows important non‐linear relationships with RA, but is not the sole predictor. Forest age effects are comparable to climate in magnitude (MAT: ß = 0.24, p = 0.021; old growth forest: ß = 0.22, p p = 0.001; soil N: ß = −0.07, p = 0.001). These results provide strong evidence that ecosystem‐scale RA is mediated by climate, forest age, and soil conditions, and is not a globally fixed fraction of positive NPP as assumed by most vegetation and ecosystem models. Our dataset and findings can be used by modellers to improve predictions of forest regeneration and carbon cycling.

A Multivariate and Network Analysis Uncovers a Long-Term Influence of Exclusive Breastfeeding on the Development of Brain Morphology and Structural Connectivity - Fabrizio Parente; Tiziana Pedale; Camilla Rossi-Espagnet; Daniela Longo; Antonio Napolitano; Simone Gazzellini; Simone Macrì; Valerio Santangelo (Brain Topography, 2025)

Does the conservation of threatened species limit crop production? On farm cultivation of Marsilea quadrifolia in rice fields - Anna Corli; Thomas Abeli; Graziano Rossi; Valentina Vaglia; Luca Favino; Riccardo Frati; Simone Orsenigo (Paddy and Water Environment, 2025)

Association between long-term exposure to air pollution and cause-specific mortality within five Italian longitudinal metropolitan studies - Federica Nobile; Nicola Caranci; Elena Strippoli; Valentina Adorno; Alessandra Allotta; Lucia Bisceglia; Ida Galise; Claudio Gariazzo; Sara Maio; Paola Michelozzi; Walter Pollina Addario; Andrea Ranzi; et al. (Atmospheric Environment, 2024)

Driving EU sustainability: Promoting the circular economy through municipal waste efficiency - Idiano D'Adamo; Cinzia Daraio; Simone Di Leo; Massimo Gastaldi; Edouard Nicolas Rossi (Sustainable Production and Consumption, 2024)

Best practices, errors, and perspectives of half a century of plant translocation in Italy - Martina D'Agostino; Luigi Cao Pinna; Marta Carboni; Silvia Assini; Gianluigi Bacchetta; Fabrizio Bartolucci; Lisa Brancaleoni; Fabrizio Buldrini; Angelino Carta; Bruno Cerabolini; Roberta Maria Ceriani; Umberto Clementi; et al. (Conservation Biology, 2024)
Conservation translocations are becoming common conservation practice, so there is an increasing need to understand the drivers of plant translocation performance through reviews of cases at global and regional levels. The establishment of the Italian Database of Plant Translocation (IDPlanT) provides the opportunity to review the techniques used in 186 plant translocation cases performed in the last 50 years in the heart of the Mediterranean Biodiversity Hotspot. We described techniques and information available in IDPlanT and used these data to identify drivers of translocation outcomes. We tested the effect of 15 variables on survival of translocated propagules as of the last monitoring date with binomial logistic mixed‐effect models. Eleven variables significantly affected survival of transplants: life form, site protection, material source, number of source populations, propagation methods, propagule life stage, planting methods, habitat suitability assessment, site preparation, aftercare, and costs. The integration of vegetation studies in the selection of suitable planting sites significantly increased the success of translocation efforts. Although posttranslocation watering had a generally positive effect on translocation outcome, other aftercare techniques did not always increase transplant survival. Finally, we found that how funds were spent appeared to be more important than the actual amount spent. Plant translocations in Italy and in the Mediterranean area should account for the complexity of speciation, gene flow, and plant migrations that has led to local adaptations and has important implications for the choice and constitution of source material.

Fertilisation increases plant biomass and seed production but does not influence seed heteromorphism in Aegilops - Thomas Abeli; Filippo Guzzon; Simone Orsenigo; Graziano Rossi (Plant Biosystems, 2024)

Evaluation of the point sampling method and inter-comparison of remote emission sensing systems for screening real-world car emissions - Markus Knoll; Martin Penz; Christina Schmidt; Denis Pöhler; Tommaso Rossi; Simone Casadei; Yoann Bernard; Ǻsa M. Hallquist; Ǻke Sjödin; Alexander Bergmann (Science of The Total Environment, 2024)

Germination niche of co-occurring threatened native and alien species: a case study in Lindernia procumbens and L. dubia - Anna Corli; Simone Orsenigo; Francesco Porro; Graziano Rossi; Silvano Lodetti; Andrea Mondoni (Plant Ecology, 2024)
Plant invasions have a negative impact on biodiversity and lead to species loss. Although studies on traits promoting invasiveness have been largely developed, comparative studies on germination traits of closely related native versus alien invasive species, which also take into account threatened species, are lacking. We analysed the germination requirements of two congeneric Lindernia species inhabiting paddy field in Northern Italy. Germination tests were conducted exposing seeds of both species across a broad range of temperature and conditions (i.e., cold-wet stratification, dark condition, alternate temperature, gibberellic acid). The invasive L. dubia showed higher and faster germination, occurring over a broader range of temperatures compared to the native threatened L. procumbens , along with a lighter non-deep physiological dormancy. These results show a competitive advantage of the alien species already in the early stages of plant regeneration and provide a comprehensive overview of the germination requirements, necessary for the development of future conservation and management plans.

Nitrogen loss abatement from dairy cow excreta through urine and faeces separation: The effect of temperature and exposure period on NH3 fluxes - Valentina Becciolini; Lorenzo Leso; Esperanza Fuertes Gimeno; Giuseppe Rossi; Matteo Barbari; Anna Dalla Marta; Simone Orlandini; Leonardo Verdi (Agricultural Systems, 2024)

Life cycle assessment of biostimulant production from algal biomass grown on piggery wastewater - Elena M. Rojo; Simone Rossi; Silvia Bolado; Paola Gallo Stampino; Elena Ficara; Giovanni Dotelli (Science of The Total Environment, 2024)

Removal of pharmaceutical compounds from the liquid phase of anaerobic sludge in a pilot-scale high-rate algae-bacteria pond - Marco Mantovani; Simone Rossi; Elena Ficara; Elena Collina; Francesca Marazzi; Marina Lasagni; Valeria Mezzanotte (Science of The Total Environment, 2024)

A new approach for assessing winning and losing plant species facing climate change on the GLORIA alpine summits - Silvano Lodetti; Simone Orsenigo; Brigitta Erschbamer; Angela Stanisci; Marcello Tomaselli; Alessandro Petraglia; Michele Carbognani; Valter di Cecco; Luciano di Martino; Graziano Rossi; Francesco Porro (Flora, 2024)

Concentrations of polycyclic aromatic hydrocarbons (PAHs) in liver samples of green turtles Chelonia mydas stranded in the Potiguar Basin, northeastern Brazil - Silmara Rossi; Daniel Solon Dias de Farias; Aline da Costa Bomfim; Renato S. Carreira; José Henrique Hildebrand Grisi-Filho; Carlos G. Massone; Flávio José de Lima Silva; Simone Almeida Gavilan (Marine Pollution Bulletin, 2023)

The use of an alimentary index to assess anthropogenic debris on green turtles (Chelonia mydas) - Daniel Solon Dias de Farias; Aline da Costa Bomfim Ventura; Flávio José de Lima Silva; Raquel Marinho de Souza Cavalcante; Silmara Rossi; Simone Almeida Gavilan; Vinícius Gabriel da Silva Santana; Viviane Souza do Amaral (Marine Pollution Bulletin, 2023)

Cats and clouds: how a citizen camera-trapping project boosts wildcat (Felis silvestris) conservation - Sara Savazza; Paolo Rossi; Nicola Rebora; Fabrizio G. Lioy; Donato Franculli; Andrè Roveyaz; Alfredo Bruno; Antonio Sicuro; Giuseppe Dino; Erica La Placa; Lorenzo Gaudiano; Luciano Cicognani; et al. (European Journal of Wildlife Research, 2023)

A multivariate approach to dithiocarbamate fungicides determination in yerba mate (Ilex paraguariensis): A faster, cheaper, robust, and environmentally friendly method - Rosselei Caiel da Silva; Júlia Paula Neu; Ingrid Duarte dos Santos; Paola Jennifer Babinski; Rochele Cassanta Rossi; Jessica Fernanda Hoffmann; Roger Wagner; Simone Noremberg Kunz; Ionara Regina Pizzutti (Food Chemistry, 2023)

First report on classical biological control releases of the larval parasitoid Ganaspis brasiliensis against Drosophila suzukii in northern Italy - Lorenzo Fellin; Alberto Grassi; Simone Puppato; Alberto Saddi; Gianfranco Anfora; Claudio Ioriatti; Marco Valerio Rossi-Stacconi (BioControl, 2023)
Current management strategy of the invasive fruit fly Drosophila suzukii (Matsumura) (Diptera: Drosophilidae) exploits different tools but relies mainly on chemical control. In the invaded areas, the local natural enemy community mostly consists of generalist pupal parasitoids unable to control the pest efficiently. Conversely, in the pest native area, there are more specialized sympatric larval parasitoids attacking D. suzukii . Following foreign explorations and quarantine risk assessments, the larval endoparasitoid Ganaspis brasiliensis (Ihering) (Hymenoptera: Figitidae) was selected as the best candidate for classical biological control programs. In 2021, the first ever propagative biocontrol program using a Japanese G1 lineage of G. brasiliensis started in Italy. Here we report the results of the first year of releases in the province of Trento (Northeast Italy), wherein G. brasiliensis was released in 12 locations. Pre- and post-release samplings on fresh and fallen fruits were performed around the release points to assess the recapture rate, the impact of the exotic parasitoid on D. suzukii and its potential interactions with local non-target species. After releases, G. brasiliensis was recovered at 50% of the locations. The exotic parasitoid only emerged from D. suzukii , mostly from fresh fruit still on the plant. Post-overwintering monitoring revealed the presence of a four G. brasiliensis individuals at two release locations.

Relative importance of site selection and aftercare for successful reintroduction of the policy species Kosteletzkya pentacarpos - Anna Corli; Renato Gerdol; Simone Orsenigo; Graziano Rossi; Thomas Abeli; Paola Iacumin; Roberta Marchesini; Lisa Brancaleoni (Plant Biosystems, 2023)

Late Quaternary sedimentary record of estuarine incised-valley filling and interfluve flooding: The Manfredonia paleovalley system (southern Italy) - Alessandro Amorosi; Luigi Bruno; Massimo Caldara; Bruno Campo; Simone Cau; Vincenzo De Santis; Andrea Di Martino; Wan Hong; Giorgio Lucci; Claudio Pellegrini; Veronica Rossi; Irene Sammartino; et al. (Marine and Petroleum Geology, 2023)

Association between short-term exposure to air pollutants and cause-specific daily mortality in Italy. A nationwide analysis - Claudio Gariazzo; Matteo Renzi; Alessandro Marinaccio; Paola Michelozzi; Stefania Massari; Camillo Silibello; Giuseppe Carlino; Paolo Giorgi Rossi; Sara Maio; Giovanni Viegi; Massimo Stafoggia; Sandra Baldacci; et al. (Environmental Research, 2023)

Chicken embryos are a valuable model for the selection of Bacillus subtilis for probiotic purposes - Thais Fernanda Martins dos Reis; Patricia Giovana Hoepers; Vasco Ariston de Carvalho Azevedo; Gabriela Ribeiro da Silva; Fabiana Oliveira Notário; Maria Cecília Soares; André Eduardo Schlemper; Ícaro Mendonça Costa; Nina Dias Coelho-Rocha; Mylla Spirandelli da Costa; Simone Sommerfeld; Alessandra Aparecida Medeiros-Ronchi; et al. (Archives of Microbiology, 2022)

Embedded Computational Heart Model for External Ventricular Assist Device Investigations - Thomas Kummer; Simone Rossi; Stijn Vandenberghe; Stefanos Demertzis; Patrick Jenny (Cardiovascular Engineering and Technology, 2022)
Purpose External cardiac assist devices are based on a promising and simple concept for treating heart failure, but they are surprisingly difficult to design. Thus, a structured approach combining experiments with computer-based optimization is essential. The latter provides the motivation for the work presented in this paper. Methods We present a computational modeling framework for realistic representation of the heart’s tissue structure, electrophysiology and actuation. The passive heart tissue is described by a nonlinear anisotropic material law, considering fiber and sheetlet directions. For muscle contraction, an orthotropic active-strain model is employed, initiated by a periodically propagating electrical potential. The model allows for boundary conditions at the epicardium accounting for external assist devices, and it is coupled to a circulation network providing appropriate pressure boundary conditions inside the ventricles. Results Simulated results from an unsupported healthy and a pathological heart model are presented and reproduce accurate deformations compared to phenomenological measurements. Moreover, cardiac output and ventricular pressure signals are in good agreement too. By investigating the impact of applying an exemplary external actuation to the pathological heart model, it shows that cardiac patches can restore a healthy blood flow. Conclusion We demonstrate that the devised computational modeling framework is capable of predicting characteristic trends (e.g. apex shortening, wall thickening and apex twisting) of a healthy heart, and that it can be used to study pathological hearts and external activation thereof.

Peripheral neuropathies during the COVID-19 pandemic: is there a relation? - Milena Trentinaglia; Giuseppe Lippi; Gian Luca Salvagno; Marianna G. Rispoli; Maria Vittoria De Angelis; Francesca Castellani; Daniela Alberti; Giorgia T. Maniscalco; Francesca Rossi; Mara Turri; Patrizia Rossi; Elisabetta Del Zotto; et al. (Immunologic Research, 2022)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Amelioration of salt stress tolerance in rapeseed ( Brassica napus ) cultivars by seed inoculation with Arthrobacter globiformis - Panaiotis M. Stassinos; Massimiliano Rossi; Ilaria Borromeo; Concetta Capo; Simone Beninati; Cinzia Forni (Plant Biosystems, 2022)

Seed germination under osmotic stress across different wild populations of mountain rye ( Secale strictum (C.Presl) C.Presl)) - Graziano Rossi; Filippo Guzzon; Charlotte Bickler; Paolo Cauzzi; Luciano Di Martino; Valter Di Cecco; Gianniantonio Domina; Domenico Gargano; Ilda Vagge; Simone Orsenigo; Jonas V. Müller (Plant Biosystems, 2022)

Chronic exposure to lead acetate promotes changes in the alveolar bone of rats: microstructural and physical–chemical characterization - Lodinikki Lemoy Davis; Walessa Alana Bragança Aragão; Géssica de Oliveira Lopes; Luciana Guimaraes Eiró; Alexandre Rodrigues Freire; Felippe Bevilacqua Prado; Ana Cláudia Rossi; Allan da Silva Cruz; Kelly das Graças Fernandes Dantas; Alan Rodrigo Leal Albuquerque; Simone Patricia Aranha Paz; Rômulo Simões Angélica; et al. (Environmental Science and Pollution Research, 2022)

Richer, greener, and more thermophilous? – a first overview of global warming induced changes in the Italian alpine plant communities within the new GLORIA ITALIA NETWORK - Francesco Porro; Simone Orsenigo; Thomas Abeli; Andrea Mondoni; Anna Corli; Fiona J. White; Silvano Lodetti; Marcello Tomaselli; Alessandro Petraglia; Michele Carbognani; Matteo Gualmini; T’ai G. W. Forte; et al. (Plant Biosystems, 2022)

IDPlanT: the Italian database of plant translocation - Thomas Abeli; Martina D’Agostino; Simone Orsenigo; Fabrizio Bartolucci; Rita Accogli; Giulia Albani Rocchetti; Claudia Alessandrelli; Arianna Amadori; Filippo Amato; Claudia Angiolini; Silvia Assini; Gianluigi Bacchetta; et al. (Plant Biosystems, 2021)

Conservation status of the Italian flora under the 92/43/EEC ‘Habitats’ Directive - Giuseppe Fenu; Consolata Siniscalco; Gianluigi Bacchetta; Donatella Cogoni; Maria Silvia Pinna; Marco Sarigu; Thomas Abeli; Elena Barni; Fabrizio Bartolucci; Daniela Bouvet; Annalena Cogoni; Fabio Conti; et al. (Plant Biosystems, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Coexistence of rice production and threatened plant species: testing Marsilea quadrifolia L. in N-Italy - Anna Corli; Simone Orsenigo; Renato Gerdol; Stefano Bocchi; Alfons P. Smolders; Lisa Brancaleoni; Maria Teresa Caffi; Thomas Abeli; Graziano Rossi (Paddy and Water Environment, 2021)
In the past, the aquatic pteridophyte Marsilea quadrifolia L. was considered as a weed in paddy fields of southern Europe. The systematic use of herbicides as a crucial component of intensive agronomic approach has led to a dramatic decline in M. quadrifolia populations in European countries, mostly in the Mediterranean area. However, the introduction in recent years of sustainable rice cultivation practices has allowed partial recovery. We present here the results of a research aimed at analyzing the effects of farming typologies in respect to M. quadrifolia growth in the Po Valley area. After having transplanted M. quadrifolia swards in rice fields belonging to different farming systems, we monitored its growth and diffusion. Our results showed that M. quadrifolia has higher vegetative performance in organic farms, even though it can survive in conventional fields with reduced herbicide supply. Differences in water chemistry have limited effects on M. quadrifolia performance, because of its wide ecological amplitude. The shady conditions provided by rice canopy create micro-habitats suitable for M. quadrifolia growth. Cultivating M. quadrifolia in organic rice farms represents an important opportunity for preserving this endangered species in areas of intensive agriculture. This can, meanwhile, represent a valid opportunity to combine nature conservation and productivity offering a new possible income for farmers.

Long-lasting connectivity changes induced by intensive first-person shooter gaming - Davide Momi; Carmelo L. Smeralda; Giorgio Di Lorenzo; Francesco Neri; Simone Rossi; Alessandro Rossi; Emiliano Santarnecchi (Brain Imaging and Behavior, 2021)

Red list of threatened vascular plants in Italy - Simone Orsenigo; Giuseppe Fenu; Domenico Gargano; Chiara Montagnani; Thomas Abeli; Alessandro Alessandrini; Gianluigi Bacchetta; Fabrizio Bartolucci; Angelino Carta; Miris Castello; Donatella Cogoni; Fabio Conti; et al. (Plant Biosystems, 2021)

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Benefits of conservation-driven mowing for the EU policy species Gladiolus palustris Gaudin in mountain fen meadows: a case-study in the European Alps - Marco Canella; Gianni Poloniato; Cesare Lasen; Simone Orsenigo; Graziano Rossi; Jonas V. Müller; Thomas Abeli (Journal of Mountain Science, 2020)
The sword lily Gladiolus palustris Gaudin is protected on European level and listed in Annexes II and IV of the EC Habitat Directive 92/43/EEC. It grows in nutrient-poor, calcareous meadows in central and eastern Europe. Tree encroachment in montane meadows of the European Alps as a result of recent land use changes and the abandonment of traditional farming practices threaten the survival of this species. Conservation-driven mowing is considered a feasible conservation measure for maintaining high species diversity in abandoned semi-natural grasslands. To assess the effects of ten years of biennial mowing on a grassland community in the Dolomiti Bellunesi National Park, Italy (Site of Community Importance, Natura 2000 network), ten 25 m 2 plots were established whereby four plots were placed in the mowed area, four in the non-mowed area and two in a small non-mowed patch of grassland inside the mowed area. In each plot the following variables were recorded, total percentage of plant cover, percentage cover of woody species, percentage cover of herbaceous species, percentage cover and number of flowering ramets of G. palustris and a complete list of species and their percentage abundance. Mowed plots showed a higher species richness than non-mowed plots. The number of G. palustris flowering ramets and percentage cover increased manifold in mowed plots compared to non-mowed plots. The resumption of mowing for conservation purposes undertaken by the managing authority halted the process of tree encroachment and avoided a drastic change in plant composition. Periodic mowing (every second or third year) was demonstrated to be a cost-effective conservation measure in non-productive grasslands to keep grasses at bay in favour of forbs of high conversation value.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

New estimates of greenhouse gas emissions from biomass burning and peat fires using MODIS Collection 6 burned areas - Paolo Prosperi; Mario Bloise; Francesco N. Tubiello; Giulia Conchedda; Simone Rossi; Luigi Boschetti; Mirella Salvatore; Martial Bernoux (Climatic Change, 2020)
The Paris Agreement calls on parties to undertake ambitious efforts to combat climate change by engaging in appropriate policies and measures as put forward through Nationally Determined Contributions (NDCs), to strengthen transparency when reporting their greenhouse gas (GHG) emissions and to increase their mitigation contributions to climate action from 2020. It also calls for regular and transparent monitoring and reporting of the GHG emissions and on the NDCs implementation efforts. Biomass fires significantly affect the GHG atmospheric balance, with fire emissions representing more than 5% of total emissions from agriculture, forestry, and other land use (AFOLU), according to recent estimates produced by the Food and Agriculture Organization (FAO). We update previously published Tier 1 estimates of GHG emissions in FAOSTAT—which had been used in the IPCC AR5 analysis—by using new burned area activity data from the Moderate Resolution Imaging Spectroradiometer (MODIS) known as MCD64A1, Collection 6. The previous FAOSTAT estimates had used as input the Global Fire Emission Database v.4 (GFED4) burned area product, based on older MODIS Collection 5.1 burned area product. In line with differences between the input data used, the new FAOSTAT estimates indicate roughly 30% higher fire emissions globally than previously published. Our analysis also confirms that the FAOSTAT Tier 1 approach produces fire emissions estimates that are comparable to those computed at Tier 3 by GFED, and thus represent a useful complementary tool in support of country GHG reporting.

Assessing the Effect of Contaminated and Restored Marine Sediments in Different Experimental Mesocosms Using an Integrated Approach and Mytilus galloprovincialis as a Model - Stefania Ancora; Federica Rossi; Marina Borgese; Cristina Pirrone; Ilaria Caliani; Simone Cappello; Giuseppe Mancini; Nicola Bianchi; Claudio Leonzio; Giovanni Bernardini; Rosalba Gornati (Marine Biotechnology, 2020)

Fluid–Structure Interaction Models of Bioprosthetic Heart Valve Dynamics in an Experimental Pulse Duplicator - Jae H. Lee; Alex D. Rygg; Ebrahim M. Kolahdouz; Simone Rossi; Stephen M. Retta; Nandini Duraiswamy; Lawrence N. Scotten; Brent A. Craven; Boyce E. Griffith (Annals of Biomedical Engineering, 2020)
Computer modeling and simulation is a powerful tool for assessing the performance of medical devices such as bioprosthetic heart valves (BHVs) that promises to accelerate device design and regulation. This study describes work to develop dynamic computer models of BHVs in the aortic test section of an experimental pulse-duplicator platform that is used in academia, industry, and regulatory agencies to assess BHV performance. These computational models are based on a hyperelastic finite element extension of the immersed boundary method for fluid–structure interaction (FSI). We focus on porcine tissue and bovine pericardial BHVs, which are commonly used in surgical valve replacement. We compare our numerical simulations to experimental data from two similar pulse duplicators, including a commercial ViVitro system and a custom platform related to the ViVitro pulse duplicator. Excellent agreement is demonstrated between the computational and experimental results for bulk flow rates, pressures, valve open areas, and the timing of valve opening and closure in conditions commonly used to assess BHV performance. In addition, reasonable agreement is demonstrated for quantitative measures of leaflet kinematics under these same conditions. This work represents a step towards the experimental validation of this FSI modeling platform for evaluating BHVs.

Ex situ collections and their potential for the restoration of extinct plants - Thomas Abeli; Sarah Dalrymple; Sandrine Godefroid; Andrea Mondoni; Jonas V. Müller; Graziano Rossi; Simone Orsenigo (Conservation Biology, 2020)
The alarming current and predicted species extinction rates have galvanized conservationists in their efforts to avoid future biodiversity losses, but for species extinct in the wild, few options exist. We posed the questions, can these species be restored, and, if so, what role can ex situ plant collections (i.e., botanic gardens, germplasm banks, herbaria) play in the recovery of plant genetic diversity? We reviewed the relevant literature to assess the feasibility of recovering lost plant genetic diversity with using ex situ material and the probability of survival of subsequent translocations. Thirteen attempts to recover species extinct in the wild were found, most of which used material preserved in botanic gardens (12) and seed banks (2). One case of a locally extirpated population was recovered from herbarium material. Eight (60%) of these cases were successful or partially successful translocations of the focal species or population; the other 5 failed or it was too early to determine the outcome. Limiting factors of the use of ex situ source material for the restoration of plant genetic diversity in the wild include the scarcity of source material, low viability and reduced longevity of the material, low genetic variation, lack of evolution (especially for material stored in germplasm banks and herbaria), and socioeconomic factors. However, modern collecting practices present opportunities for plant conservation, such as improved collecting protocols and improved cultivation and storage conditions. Our findings suggest that all types of ex situ collections may contribute effectively to plant species conservation if their use is informed by a thorough understanding of the aforementioned problems. We conclude that the recovery of plant species currently classified as extinct in the wild is not 100% successful, and the possibility of successful reintroduction should not be used to justify insufficient in situ conservation.

Mesocosm System to Evaluate BF-MBR Efficacy in Mitigating Oily Wastewater Discharges: an Integrated Study on Mytilus galloprovincialis - Rosalba Gornati; Maria Maisano; Cristina Pirrone; Tiziana Cappello; Federica Rossi; Marina Borgese; Alessia Giannetto; Simone Cappello; Giuseppe Mancini; Giovanni Bernardini; Salvatore Fasulo (Marine Biotechnology, 2019)

Plant–environment interactions through a functional traits perspective: a review of Italian studies - Stefano Chelli; Michela Marignani; Elena Barni; Alessandro Petraglia; Giacomo Puglielli; Camilla Wellstein; Alicia T. R. Acosta; Rossano Bolpagni; Luca Bragazza; Giandiego Campetella; Alessandro Chiarucci; Luisa Conti; et al. (Plant Biosystems, 2019)

Could plant diversity metrics explain climate-driven vegetation changes on mountain summits of the GLORIA network? - Francesco Porro; Marcello Tomaselli; Thomas Abeli; Maurizia Gandini; Matteo Gualmini; Simone Orsenigo; Alessandro Petraglia; Graziano Rossi; Michele Carbognani (Biodiversity and Conservation, 2019)

Evaluation of the displacement ductility for the seismic design of light-frame wood buildings - Simone Rossi; Ivan Giongo; Daniele Casagrande; Roberto Tomasi; Maurizio Piazza (Bulletin of Earthquake Engineering, 2019)

Anthropogenic and environmental factors affect the tree line position of Fagus sylvatica along the Apennines (Italy) - Giuliano Bonanomi; Angelo Rita; Emilia Allevato; Gaspare Cesarano; Luigi Saulino; Gaetano Di Pasquale; Marina Allegrezza; Simone Pesaresi; Marco Borghetti; Sergio Rossi; Antonio Saracino (Journal of Biogeography, 2018)
Aim High‐elevation forest line or tree line is an ecological ecotone representing the upper elevation thermal limit for forest development. The current tree line position is the result of the past human activity interacting with climatic and topographic conditions. In this study, we investigate how climate, local topographic factors and anthropogenic disturbance currently affect tree line distribution. Location Apennine Mountains, 900 km latitudinal gradient along the Italian Peninsula. Methods Overall, 302 mountain peaks were studied, comprising 3,622 km of measured tree lines. The position of the Fagus sylvatica tree line in all peaks was assessed and correlated with 58 selected variables representing climate, topography and human disturbance. Results The mean tree line elevation was 1,589 m a.s.l., with considerable variability among peaks. Contrary to our expectations, the tree line elevation was lower in the warmer southerly exposed slopes compared to north‐facing aspects, where we found the highest tree line (2,141 m a.s.l.). Correlation analysis indicates that both climatic and human density variables are associated with tree line elevation, with the climate having more influence in high elevation mountains, while human impact plays a prominent role in low elevation mountain peaks. Specifically, we found negative correlations between density of the resident population around each peak and tree line elevation at all examined dates (1861, 1921, and 2011), suggesting a pervasive negative impact of human activity on tree lines. As regards climatic variables, tree line elevation showed a stronger negative correlation with winter and spring months temperature than with mean annual temperature. Noteworthy, climatic variables had stronger effect on high elevation peaks (>1,900 m a.s.l.) compared with low elevation ones ( Main Conclusion Our data provide evidence that the current position of the F. sylvatica tree line in the Apennines is heavily depressed as a result of a complex interaction between climatic factors and the past human pressure.

Deregulation of autophagy under hyperglycemic conditions is dependent on increased lysine 63 ubiquitination: a candidate mechanism in the progression of diabetic nephropathy - Paola Pontrelli; Annarita Oranger; Mariagrazia Barozzino; Chiara Divella; Francesca Conserva; Maria Grazia Fiore; Roberta Rossi; Massimo Papale; Giuseppe Castellano; Simona Simone; Luigi Laviola; Francesco Giorgino; et al. (Journal of Molecular Medicine, 2018)

Multiclass methods for the analysis of antibiotic residues in milk by liquid chromatography coupled to mass spectrometry: A review - Rosanna Rossi; Giorgio Saluti; Simone Moretti; Irene Diamanti; Danilo Giusepponi; Roberta Galarini (Food Additives & Contaminants: Part A, 2018)

PCA-based artifact removal algorithm for stroke detection using UWB radar imaging - Elisa Ricci; Simone di Domenico; Ernestina Cianca; Tommaso Rossi; Marina Diomedi (Medical & Biological Engineering & Computing, 2017)

Role of brain hemispheric dominance in anticipatory postural control strategies - David Cioncoloni; Deborah Rosignoli; Matteo Feurra; Simone Rossi; Marco Bonifazi; Alessandro Rossi; Riccardo Mazzocchio (Experimental Brain Research, 2016)

Erratum to: FAOSTAT estimates of greenhouse gas emissions from biomass and peat fires - Simone Rossi; Francesco N. Tubiello; Paolo Prosperi; Mirella Salvatore; Heather Jacobs; Riccardo Biancalani; Joanna I. House; Luigi Boschetti (Climatic Change, 2016)

FAOSTAT estimates of greenhouse gas emissions from biomass and peat fires - Simone Rossi; Francesco N. Tubiello; Paolo Prosperi; Mirella Salvatore; Heather Jacobs; Riccardo Biancalani; Joanna I. House; Luigi Boschetti (Climatic Change, 2016)

Therapeutic drug monitoring of second-generation antipsychotics in pediatric patients: an observational study in real-life settings - Marco Pozzi; Dario Cattaneo; Sara Baldelli; Serena Fucile; Annalisa Capuano; Carmela Bravaccio; Liberata Sportiello; Silvana Bertella; Fabiana Auricchio; Renato Bernardini; Carmen Ferrajolo; Giuseppe Guastella; et al. (European Journal of Clinical Pharmacology, 2016)

Restoring population structure and dynamics in translocated species: learning from wild populations - Thomas Abeli; Paolo Cauzzi; Graziano Rossi; Michele Adorni; Ilda Vagge; Gilberto Parolo; Simone Orsenigo (Plant Ecology, 2016)

The Contribution of Agriculture, Forestry and other Land Use activities to Global Warming, 1990–2012 - Francesco N. Tubiello; Mirella Salvatore; Alessandro F. Ferrara; Jo House; Sandro Federici; Simone Rossi; Riccardo Biancalani; Rocio D. Condor Golec; Heather Jacobs; Alessandro Flammini; Paolo Prosperi; Paola Cardenas‐Galindo; et al. (Global Change Biology, 2015)
We refine the information available through the IPCC AR 5 with regard to recent trends in global GHG emissions from agriculture, forestry and other land uses ( AFOLU ), including global emission updates to 2012. Using all three available AFOLU datasets employed for analysis in the IPCC AR 5, rather than just one as done in the IPCC AR 5 WGIII Summary for Policy Makers, our analyses point to a down‐revision of global AFOLU shares of total anthropogenic emissions, while providing important additional information on subsectoral trends. Our findings confirm that the share of AFOLU emissions to the anthropogenic total declined over time. They indicate a decadal average of 28.7 ± 1.5% in the 1990s and 23.6 ± 2.1% in the 2000s and an annual value of 21.2 ± 1.5% in 2010. The IPCC AR 5 had indicated a 24% share in 2010. In contrast to previous decades, when emissions from land use (land use, land use change and forestry, including deforestation) were significantly larger than those from agriculture (crop and livestock production), in 2010 agriculture was the larger component, contributing 11.2 ± 0.4% of total GHG emissions, compared to 10.0 ± 1.2% of the land use sector. Deforestation was responsible for only 8% of total anthropogenic emissions in 2010, compared to 12% in the 1990s. Since 2010, the last year assessed by the IPCC AR 5, new FAO estimates indicate that land use emissions have remained stable, at about 4.8 Gt CO 2 eq yr −1 in 2012. Emissions minus removals have also remained stable, at 3.2 Gt CO 2 eq yr −1 in 2012. By contrast, agriculture emissions have continued to grow, at roughly 1% annually, and remained larger than the land use sector, reaching 5.4 Gt CO 2 eq yr −1 in 2012. These results are useful to further inform the current climate policy debate on land use, suggesting that more efforts and resources should be directed to further explore options for mitigation in agriculture, much in line with the large efforts devoted to REDD+ in the past decade.

Some like it hot and some like it cold, but not too much: plant responses to climate extremes - Simone Orsenigo; Andrea Mondoni; Graziano Rossi; Thomas Abeli (Plant Ecology, 2014)

Effects of marginality on plant population performance - Thomas Abeli; Rodolfo Gentili; Andrea Mondoni; Simone Orsenigo; Graziano Rossi (Journal of Biogeography, 2014)
Aim Populations at the edge of a species' distribution range may differ substantially from central populations. Peripheral populations may have either a high evolutionary potential or be prone to extinction, but the processes driving these outcomes are still unclear. Peripheral plant populations have been the subject of numerous studies and reviews, with many focusing on their genetic characteristics. In this review, we consider the effect of marginality on demographic species‐specific traits. Location World‐wide. Methods We reviewed the literature based on direct comparisons between central and peripheral plant populations. Strict inclusion criteria were applied to avoid biased analysis that may arise as a result of inaccurate boundary considerations or inappropriate comparisons. We inferred from the published data whether a certain trait had a better performance in central or peripheral populations (reliability of the abundant centre hypothesis, ACH ). Results There have not been enough studies on plant performance to allow for generalizations on the effects of marginality on plants. ACH expectations were not met in most cases and specific responses to marginality were observed at the species and population levels. Population and plant size more often met the ACH assumptions, suggesting that most geographically peripheral populations are also ecologically marginal. The availability of resources, the reproductive strategy, the level of ploidy and the ability to cope with interspecific competitors seem to drive the numerous exceptions to the ACH expectations. Main conclusions The large numbers of exceptions to the ACH expectations suggest that a new comprehensive theory is needed to explain the effects of marginality in plants and to identify any general patterns. From the theoretical point of view, we propose that population history and dynamics should be considered when attempting to explain the processes that occur in peripheral plant populations.

8-Isoprostane, prostaglandin E2, C-reactive protein and serum amyloid A as markers of inflammation and oxidative stress in antiphospholipid syndrome: a pilot study - Savino Sciascia; Dario Roccatello; Maria Tiziana Bertero; Debora Di Simone; Domenico Cosseddu; Antonella Vaccarino; Mario Bazzan; Daniela Rossi; Cesar Garcia-Fernandez; Leticia Ceberio; Stefania Stella; Elisa Menegatti; et al. (Inflammation Research, 2012)

Innocent until proven guilty? Stable coexistence of alien rainbow trout and native marble trout in a Slovenian stream - Simone Vincenzi; Alain J. Crivelli; Dusan Jesensek; Gianluigi Rossi; Giulio A. De Leo (The Science of Nature, 2011)

Hesperidin Gastroresistant Microparticles by Spray-Drying: Preparation, Characterization, and Dissolution Profiles - Francesca Sansone; Alessandra Rossi; Pasquale Del Gaudio; Francesco De Simone; Rita Patrizia Aquino; Maria Rosaria Lauro (AAPS PharmSciTech, 2009)

Oligopeptidase B-2 from Leishmania amazonensis with an unusual C-terminal extension - Herbert Matos Guedes; Rafael Carvalho; Daniel Oliveira Gomes; Bartira Rossi-Bergmann; Salvatore De-Simone (Acta Parasitologica, 2008)
The oligopeptidase B serine protease is an important virulence factor and therapeutic target in Trypanosoma infections. Recently, the Leishmania major Genome Project identified a new oligopeptidase B that was denominated oligopeptidase B-like, herein named oligopeptidase B-2. In this study, a complete open reading frame of oligopeptidase B-2 from Leishmania amazonensis (PH8 strain) was amplified by PCR using primers designed for the oligopeptidase B-2 gene of L. major. The 2,715 bp fragment coded for a protein of 905 amino acids with a predicted molecular mass of 103,918.9 Da and theoretical pI of 5.82. The encoded protein displayed ∼96% identity with L. major and ∼75% identity with Trypanosoma cruzi and T. brucei oligopeptidases B-2, and ∼21% identity with Escherichia coli and L. amazonensis classical oligopeptidase B. An unusual C-terminal extension was found in relation to the classical trypanosomatid oligopeptidase B. By sequence alignment, we determined a catalytic triad (Ser 629, Asp 717 and His 758), S1 subsite (Glu 674 and Glu 676) and suggest a difference in the S2 subsite of L. amazonensis oligopeptidase B-2. We also found that the oligopeptidase B-2 gene is expressed in all cycle stages of L. amazonensis. A phylogenetic analysis indicated that oligopeptidase B-2 is a new member of oligopeptidase B.

Environmental Security: A Geographic Information System Analysis Approach—The Case of Kenya - Stefano Bocchi; Stefano Peppino Disperati; Simone Rossi (Environmental Management, 2006)

A statistical approach to evaluate compost genotoxicity - Claudio De Simone; Rita Angelucci; Manuela Francesca Errichetti; Simona Marconi; Marcello Rossi; Sabrina Selvi (Biology and Fertility of Soils, 2005)

Neotropical wetlands: New instruments in ecosystem management - Steven A. Loiselle; Simone Bastianoni; Luca Bracchini; Claudio Rossi (Wetlands Ecology and Management, 2004)

Vibration-induced multifocal neuropathy in forestry workers: electrophysiological findings in relation to vibration exposure and finger circulation - Massimo Bovenzi; Fabio Giannini; Simone Rossi (International Archives of Occupational and Environmental Health, 2000)